Confirmation that variants in TTI2 are responsible for autosomal recessive intellectual disability. Issue 4 (17th July 2019) - Ziegler, Alban; Bader, Patricia; McWalter, Kirsty; Douglas, Ganka; Houdayer, Clara; Bris, Céline; Rouleau, Stephanie; Coutant, Régis; Colin, Estelle; Bonneau, Dominique
Abstract: TTI2 (MIM 614126) has been described as responsible for autosomal recessive intellectual disability (ID; MRT39, MIM:615541 ) in only two inbred families. Here, we give an account of two individuals from two unrelated outbred families harbouring compound heterozygous TTI2 pathogenic variants. Together with severe ID, progressive microcephaly, scoliosis and sleeping disorder are the most striking features in the two individuals concerned. TTI2, together with TTI1 and TELO2, encode proteins that constitute the triple T heterotrimeric complex. This TTT complex interacts with the HSP90 and R2TP to form a super‐complex that has a chaperone function stabilising and maturing a number of kinases, such as ataxia‐telangiectasia mutated and mechanistic target of rapamycin, which are key regulators of cell proliferation and genome maintenance. Pathogenic variants in TTI2 logically result in a phenotype close to that caused by TELO2 variants. Abstract :